Concrete integrity test using core samples for hostel & sport complex of ITM Sabah / Abdul Manaff Mohd Ismail - Mohd Ismail, Abdul Manaff (1998)
At present five (5) hostel blodes and sport complex of Mara Institute Of Technology, Kuala Menggatal, Sabah, suffers from concrete deterioration. Spalling of concrete and rusting of the steel reinforcement occur at many location in the buildings. This project focus on the study of the concrete properties of the structure. Twenty (20) core samples having diameter of 50 mm and 100 mm were given by specialist engaged in the study of the structure integrity of the said buildings. In this study, compressive strength, carbonation depth, chloride content, cement content, water absorption and UPV tests were carned out to asses the integrity of the concrete structures. To classify the integrity of the structure from the results of the tests performed, integrity factor (J) is proposed.